Production of Shistosoma mansoni cercariae by Biomphalaria glabrata from a focus in Belo Horizonte, Minas Gerais Produção de cercárias de Schistosoma mansoni por Biomphalaria glabrata de foco em Belo Horizonte, Minas Gerais - Cecília Pereira de Souza; Neusa Araújo; Liana Konovaloff Jannotti-Passos; Carlos Tito Guimarães (Revista do Instituto de Medicina Tropical de São Paulo, 1994)
The snail density, levels of infection and the monthly production of Schistosoma mansoni cercariae by Biomphalaria glabrata were determined in a focus of Barreiro de Baixo (Belo Horizonte, MG, Brazil). During a period of 38 months (1984 to 1987) 5,366 snails were collected of which 324 (6.03%) were infected with S. mansoni. The total number of cercariae shed was 5,667,312. Each snail shed an average of 17,422 cercariae during the time that it was under study in the laboratory. The greatest longevity of infected snails was 218 days. Natural cure was observed in 42 (12.9%) of the infected specimens about 130 days after collection. The average snail density in the focus during the period of study was 16.3 snails per scoop. The shedding of cercariae by snails collected from the field was compared with laboratory bred specimens infected in mass with the LE strain of S. mansoni from Belo Horizonte. The laboratory infected snails shed an average of 6,061 cercariae each, a value 2.8 times less than the field specimens due to a shorter life span. The prevalence of schistosomiasis in the focus was 14.3%. A densidade planorbídica, as taxas de infecção e a produção mensal de cercárias de Schistosoma mansoni por Biomphalaria glabrata, foram determinadas em foco do Barreiro de Baixo (Belo Horizonte MG, Brasil). Durante 38 meses, de 1984 a 1987, foram capturados 5.366 moluscos dentre os quais 324 (6,03%) estavam infectados com o S. mansoni. O total de cercárias eliminadas foi de 5.667.312. Cada molusco eliminou em média 17.422 cercárias durante sua permanência no laboratório. A maior longevidade dos moluscos infectados foi de 218 dias. Foi observada a cura natural de 42 (12,9%) dos exemplares infectados, após cerca de 130 dias de captura. A densidade planorbídica média, no foco durante esse período foi de 16,3 moluscos por conchada. A eliminação de cercárias pelos moluscos do campo foi comparada com a de exemplares criados no laboratório, infectados em massa com a linhagem LE de S. mansoni de Belo Horizonte. Os moluscos do ...